Comparison of health conditions treated with traditional and biomedical health care in a Quechua community in rural Bolivia - Puyvelde Luc Van; Van Damme Patrick; Sanca Sabino; Thomas Evert; Vandebroek Ina; De Kimpe Norbert (BMC, 2008)
Abstract Background The objective of the present study was to reveal patterns in the treatment of health conditions in a Quechua-speaking community in the Bolivian Andes based on plant use data from traditional healers and patient data from a primary health care (PHC) service, and to demonstrate similarities and differences between the type of illnesses treated with traditional and biomedical health care, respectively. Methods A secondary analysis of plant use data from semi-structured interviews with eight healers was conducted and diagnostic data was collected from 324 patients in the community PHC service. Health conditions were ranked according to: (A) the percentage of patients in the PHC service diagnosed with these conditions; and (B) the citation frequency of plant use reports to treat these conditions by healers. Healers were also queried about the payment modalities they offer to their patients. Results Plant use reports from healers yielded 1166 responses about 181 medicinal plant species, which are used to treat 67 different health conditions, ranging from general symptoms (e.g. fever and body pain), to more specific ailments, such as arthritis, biliary colic and pneumonia. The results show that treatment offered by traditional medicine overlaps with biomedical health care in the case of respiratory infections, wounds and bruises, fever and biliary colic/cholecystitis. Furthermore, traditional health care appears to be complementary to biomedical health care for chronic illnesses, especially arthritis, and for folk illnesses that are particularly relevant within the local cultural context. Payment from patients to healers included flexible, outcome contingent and non-monetary options. Conclusion Traditional medicine in the study area is adaptive because it corresponds well with local patterns of morbidity, health care needs in relation to chronic illnesses, cultural perceptions of health conditions and socio-economic aspects of health care. The quantitative analysis of plant use reports and patient data represents a novel approach to compare the contribution of traditional and biomedical health care to treatment of particular health conditions.